THE CAUCASUS OIL REGION IN BRITAIN’S MILITARY – POLITICAL PLANS, 1940 – 1942 (Journal of history-rus, 2025)
During the Second World War, the Caucasus region possessed not only vital energy resources but also significant geostrategic importance for both the Allies and Germany. By the first half of 1940, the French and British military leadership had developed various military-strategic plans aimed at preventing a potential alliance between Germany and the Soviet Union, as well as obstructing the transfer of the Caucasus’ oil resources to Germany. However, following Germany’s successive occupations of European countries, Britain’s primary priority shifted to the protection of the Middle East and India, regions essential for the defense of the country and the safeguarding of imperial interests, against possible enemy attacks. The strategic importance of the Caucasus for the Allies resurfaced after Germany’s invasion of the Soviet Union. On this occasion, the principal objective was the bombardment of the oil infrastructure, with the consent of the Soviet Union, to prevent it from falling into enemy hands. The most comprehensive plan of this kind was the operation codename “Velvet”, to be carried out jointly by American and British air forces. However, following the outcome of the Battle of Stalingrad, the Soviet Union rejected the plan’s implementation. The aim of this article is to examine in detail the objectives, content, and reasons for the non-implementation of the military plans prepared by Britain, either jointly with France and the United States or independently, during the years 1940-1942.